Computation of maximum hands-off control - Ikeda, Takuya; Nagahara, Masaaki (2016 SICE International Symposium on Control Systems (ISCS), 2016)
Maximum hands-off control is a control that has the minimum L 0 norm among all feasible controls. So far, we have proved that the maximum hands-off control is equivalent to the L 1 -optimal control under the normality assumption and is in general equivalent to the L p -optimal control with 0 <; p <; 1. In this paper, by utilizing these results we give a numerical optimization method for the maximum hands-off control. We adopt a time discretization approach. As the complexity of the approximated problem then grows exponentially, we instead solve the equivalent L 1 or L p -optimization. Under the normality assumption we apply the alternating direction method of multipliers (ADMM) for the maximum hands-off control, and otherwise we apply the successive linearization algorithm (SLA).